2005
DOI: 10.2337/diacare.28.7.1604
|View full text |Cite
|
Sign up to set email alerts
|

Use of Multisystemic Therapy to Improve Regimen Adherence Among Adolescents With Type 1 Diabetes in Chronic Poor Metabolic Control

Abstract: OBJECTIVE -The aim of this study was to determine whether multisystemic therapy (MST), an intensive, home-based psychotherapy, could improve adherence and metabolic control and decrease rates of hospital utilization among adolescents with chronically poorly controlled type 1 diabetes. RESEARCH DESIGN AND METHODS-A randomized controlled trial was conducted with 127 adolescents with type 1 diabetes and chronically poor metabolic control (HbA 1c [A1C] Ն8% for the past year) who received their diabetes care in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
156
3
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(163 citation statements)
references
References 51 publications
(32 reference statements)
2
156
3
2
Order By: Relevance
“…The principles of CBT are straightforward, and clinicians can incorporate strategies based on these principles into their work with patients (66). Interventions involving CBT-based approaches have produced positive outcomes (67)(68)(69).…”
Section: Primary Interventions To Alleviate Diabetes-related Distressmentioning
confidence: 99%
“…The principles of CBT are straightforward, and clinicians can incorporate strategies based on these principles into their work with patients (66). Interventions involving CBT-based approaches have produced positive outcomes (67)(68)(69).…”
Section: Primary Interventions To Alleviate Diabetes-related Distressmentioning
confidence: 99%
“…24 They were recruited in the period between 1999 and 2004, from an endocrinology clinic within a tertiary care children's hospital located in a major Midwestern metropolitan area. Inclusion criteria were as follows: (1) diagnosed as having type 1 diabetes for Ն1 year, (2) CPMC, as defined by an average glycohemoglobin (hemoglobin A1c [HbA1c]) level of Ն8% during the year before study entry, as well as a most recent HbA1c level of Ն8%, (3) between 10 and 17 years of age, and (4) sufficient mastery of English to communicate with therapists and to complete study measures.…”
Section: Participantsmentioning
confidence: 99%
“…Results of our prior studies showed MST to be effective in improving regimen adherence and metabolic control and decreasing hospital admissions in this population. [22][23][24] The purposes of the present study were to determine the effectiveness of the MST intervention in reducing adolescent stress related to diabetes and to investigate whether participant characteristics such as age, gender, and ethnicity were related to the success of MST in reducing stress. The primary targets of the intervention were family and extrafamily barriers to good adherence (eg, low levels of parental monitoring of diabetes self-care tasks and support for completion of self-care tasks or negative family interactions regarding diabetes care).…”
mentioning
confidence: 99%
“…Following broad and narrow screening, 17 papers were considered suitable for inclusion in the review. [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] A study flow diagram of included and excluded studies is provided in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…57 The MST group also had a decreased number of inpatient admissions whereas the number of inpatient admissions increased among control group participants. Furthermore, the findings of their study in 2007 demonstrated that MST increased support for diabetes care from both primary and secondary caregivers in two-parent but not in single-parent families.…”
Section: Reviewmentioning
confidence: 91%